1998
DOI: 10.1254/jjp.77.137
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Supplementation With Eicosapentaenoic Acid Salvages Cardiomyocytes From Hypoxia/Reoxygenation-Induced Injury in Rats Fed With Fish-Oil-Deprived Diet

Abstract: Dietary supplementation of fish oil containing eicosapentaenoic acid (C20:5 n-3, EPA) and docosahexaenoic acid (C22:6 n-3, DHA) has been shown to exert protective effects on ischemic/reperfused hearts. We determined whether deprivation of fish oil from the diet paradoxically enhances susceptibility of cardiomyocytes to hypoxia/reoxygenation-induced injury and whether supplementation with either EPA or DHA overcomes such alterations. Rats were fed with fish-oil-rich (FOR) diet, fish-oil-deprived (FOD) diet alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Also, the FFA profile in heart extracts of lean and obese mice largely reflected the FA composition of the diet. In particular, levels of arachidonic acid (n‐6), a proinflammatory FA, were significantly higher, whereas levels of DHA, which is known to exert cardioprotective effects (27), were lower in heart extracts of obese mice. Palmitic acid levels, a saturated FA that induces apoptosis in cardiomyocytes (28), were approximately sevenfold higher in cardiac extracts of obese mice compared with lean mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the FFA profile in heart extracts of lean and obese mice largely reflected the FA composition of the diet. In particular, levels of arachidonic acid (n‐6), a proinflammatory FA, were significantly higher, whereas levels of DHA, which is known to exert cardioprotective effects (27), were lower in heart extracts of obese mice. Palmitic acid levels, a saturated FA that induces apoptosis in cardiomyocytes (28), were approximately sevenfold higher in cardiac extracts of obese mice compared with lean mice.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the n-3 PUFA deficient diet may increase the severity of cellular damage after zero-flow ischemia in isolated perfused rat hearts. In this respect, Nasa et al have shown that deprivation of fish oil from the diet enhances the susceptibility of cardiomyocytes to hypoxic injury (20). The mechanisms by which the n-3 PUFA deficient diet could increase the severity of myocardial ischemia are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies were inconclusive [162 -164], the vast majority reported a beneficial effect of either marine or plant n-3 PUFAs. Long-term dietary enrichment with n-3 PUFAs reduced infarct size [165 -167], improved the recovery of mechanical cardiac activity during the reestablishment of coronary flow [90, 91, 168 -173], prevented the release of creatine kinase or lactate dehydrogenase [90, 91, 169 -171, 174, 175], favoured the recovery of action potential during reoxygenation [176,177] and improved cell survival during hypoxia [178,179]. These studies thus clearly indicated that n-3 PUFAs reduce the cellular damage triggered by ischemia and reperfusion.…”
Section: Cell Damage During Ischemia and Reperfusionmentioning
confidence: 99%
“…Exogenous DHA may even be deleterious during ischemia and reperfusion [181]. The majority of studies agreed that EPA is responsible for the beneficial effects of n-3 PUFAs when compared with DHA [91, 179,181,182], although some investigations also showed a protective effect of DHA [178,183]. The higher the level of EPA in cardiac phospholipids, the greater the protection during ischemia and reperfusion [91].…”
Section: Cell Damage During Ischemia and Reperfusionmentioning
confidence: 99%